KEPERCAYAAN DAN PERLAKUAN MASYARAKAT BANJAR TERHADAP JIMAT-JIMAT PENOLAK PENYAKIT - Arni Arni (Faculty of Ushuluddin and Humanities, 2016)
This study is an important part of exploring on local valuable object development related to belief and treatment of Banjarese society in using amulets for medication. Amulets or assortment magic power stuffs are Sarigading fabric, Kalimbutuhan, Samban, Kuwari, Caping, Buyu and Sawan bracelets, rings, and Gelang barajah (a bracelet with a special mystical writing on it), Picis, Sisik Tenggiling (Fur’s a hedgehog), baju and saputangan berajah (clothes and handkerchief with a special mystical writing on it), etc. Banjares society uses the entire amulets are for therapy medium because they have a kinship relationship with the unseen people. That is there is one of the member of family has twin brother or sister when she or he was born, but one of them was gone or invisible (unseen). In addition, it is caused that they feel having a genealogy relationship with former kings in the past. Another reason why they use the amulets is because they have a kinship relationship with crocodile incarnation. This circumstance compels them to use the amulets. These belief and treatment of most Banjarese society on the amulets are believed to be used as a medium of medication for illness which cannot be cured by medic. The amulets are worned on head, neck, shoulder, arm and finger. They can be tied on waist or they are worned as usual clothes, trousers and sarung. Before the amulets use for therapy, some of them are usually scented on kemenyan (burned incense), sometimes there are also Jasmine and Cananga flowers. This magic therapy is an implementation of life style which is completely mystical magic, as well as strong fanaticism on the instinct of ancestral. Medication through the amulets or the magic power stuffs are a primitive culture which common known as dynamism, animism, fetishism, and Totemism.